SATISFACTION TOWARD LEARNING MANAGEMENT SYSTEM: EXTENDED SCALE OF EDUCATIONAL SYSTEM QUALITY - Hernando, Hendrick; Hasya, Afina (Jurnal Ekonomi dan Bisnis Airlangga, 2023)
Introduction: Consideration against educational system quality in the context of the learning management system has increased during the pandemic period. An inconsistent finding concerning the influence of educational system quality on satisfaction has been identified. To fill this gap in the existing literature, this study aims to extend the educational system quality scale and examine its influence on students' satisfaction. Methods: Based on an intensive literature review step, device flexibility was proposed as an extended indicator. To validate and examine the proposed hypothesis, this study employed the quantitative method of PLS-SEM. Data were collected from 90 students who actively used learning management systems. Results: Our findings showed that device flexibility is valid and reliable as an educational system quality indicator. Besides, our proposed hypothesis is also confirmed. Through the structural model assessment, the influence of educational system quality on students' satisfaction is found to be significant.   Conclusion and suggestion: Device flexibility has been proven as an educational system quality indicator. In order to maintain students' satisfaction, system developers are suggested to keep improving learning management system applications, primarily on smartphone devices.